a. Calculate the enthalpy of the reaction 2NO(g)+O2(g)→2NO2(g) given the following reactions and enthalpies of formation: 12N2(g)+O2(g)→NO2(g), ΔH∘A=33.2 kJ 12N2(g)+12O2(g)→NO(g), ΔH∘B=90.2 kJ Express your answer with the appropriate units.b. Calculate the enthalpy of the reaction4B(s)+3O2(g)→2B2O3(s)given the following pertinent information:B2O3(s)+3H2O(g)→3O2(g)+B2H6(g), ΔH∘A=+2035 kJ2B(s)+3H2(g)→B2H6(g), ΔH∘B=+36 kJH2(g)+12O2(g)→H2O(l), ΔH∘C=−285 kJH2O(l)→H2O(g), ΔH∘D=+44 kJExpress your answer with the appropriate units.

Respuesta :

Answer:

(A) [tex]\Delta H^{\circ }_{r}= -144 kJ[/tex]

(B) [tex]\Delta H^{\circ }_{r}= - 2552kJ[/tex]

Explanation:

(A) 2NO(g) + O₂(g) → 2NO₂(g)

[tex]1/2 N_{2}(g)+O_{2}(g)\rightarrow NO_{2}(g), \Delta H^{\circ }_{a}=33.2 kJ....equation (a)[/tex]

[tex]1/2N_{2}(g)+1/2O_{2}(g)\rightarrow NO(g), \Delta H^{\circ }_{b}=90.2 kJ ....equation (b)[/tex]  

Now, multiplying equation (a) with 2:

⇒ [tex]N_{2}(g)+2 O_{2}(g)\rightarrow 2 NO_{2}(g)....equation (a)[/tex]

Then equation b is reversed and multiplied with 2:

[tex]2 NO(g)\rightarrow N_{2}(g)+ O_{2}(g)....equation (b)[/tex]

Now by adding the equation (a) and equation (b), we get:

⇒  [tex]2 NO(g)+ \bcancel N_{2}(g)+\bcancel 2 O_{2}(g)\rightarrow 2 NO_{2}(g) +\bcancel N_{2}(g)+ \bcancel O_{2}(g)[/tex]

⇒  2NO(g) + O₂(g) → 2NO₂(g)

Therefore, the enthalpy of the reaction:

[tex]\Delta H^{\circ }_{r}= 2\times \Delta H^{\circ }_{a} - 2\times \Delta H^{\circ }_{b}[/tex]

[tex]= (2\times33.2)- (2\times90.2)=66.4 - 180.4= -144 kJ[/tex]

(B) 4B(s)+3O₂(g) → 2B₂O₃(s)    

[tex]B_{2}O_{3}(s)+3H_{2}O(g)\rightarrow 3O_{2}(g)+B_{2}H_{6}(g), \Delta H_{a }^{\circ }=+2035 kJ...equation (a)[/tex]

[tex]2B(s)+3H_{2}(g)\rightarrow B_{2}H_{6}(g), \Delta H_{b }^{\circ }= +36 kJ...equation (b)[/tex]

[tex]H_{2}(g)+1/2O_{2}(g)\rightarrow H_{2}O(l), \Delta H_{c }^{\circ }= -285 kJ...equation (c)[/tex]

[tex]H_{2}O(l)\rightarrow H_{2}O(g), \Delta H_{d }^{\circ }=+44 kJ...equation (d)[/tex]

Now multiplying equation (b) with 2, reversing equation (a) and multiplying with 2. Reversing equation (c) and (d) and multiplying both with 6.

[tex]6O_{2}(g)+2B_{2}H_{6}(g)\rightarrow 2B_{2}O_{3}(s)+6H_{2}O(g)...equation (a)[/tex]  

[tex]4B(s)+6H_{2}(g)\rightarrow 2B_{2}H_{6}(g)...equation (b)[/tex]

[tex]6H_{2}O(l)\rightarrow 6H_{2}(g)+3O_{2}(g)...equation (c)[/tex]

[tex]6H_{2}O(g)\rightarrow 6H_{2}O(l)...equation (d)[/tex]

Now by adding the equations (a), (b), (c), (d); we get:

4B(s)+3O₂(g) → 2B₂O₃(s)

Therefore, the enthalpy of the reaction:

[tex]\Delta H^{\circ }_{r}= -2\times \Delta H^{\circ }_{a} + 2\times \Delta H^{\circ }_{b} - 6 \times \Delta H_{c }^{\circ } - 6 \times \Delta H_{d }^{\circ } [/tex]

[tex]= -2\times (+2035 kJ)+ 2\times (+36 kJ) - 6 \times (-285 kJ)- 6 \times (+44 kJ) = -4070 + 72 + 1710 - 264 = - 2552kJ[/tex]

ACCESS MORE